2000
DOI: 10.1111/j.1525-1373.2000.22321.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional Fat Deposition in the Legs Is Useful as a Presumptive Marker of Antiatherogenesity in Japanese

Abstract: Abstract. To examine the pathological role of regional fat deposition in development of metabolic and cardiovascular disorders, regional fat distribution was evaluated using metabolites and hormones as measures of obesity‐related disorders. The subjects enrolled were 100 sex‐matched inpatients, who were admitted, regardless of their body mass index values, for further examination of unusual results from periodic medical screening tests, and for examination of obesity‐induced complications and treatment of obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
(22 reference statements)
1
7
0
Order By: Relevance
“…In line with this, several studies report that after control for abdominal AT and/or VAT, greater levels of LBSAT are associated with reduced risk of glucose intolerance, insulin resistance, dyslipidaemia and arterial stiffness [10][11][12][13][14][15][16]. However, extrapolation of this notion to suggest that, controlling for changes in abdominal adiposity, reductions in LBSAT during weight reduction may lead to deterioration in cardiometabolic profile, and thus increase the risk of type 2 diabetes and cardiovascular disease, counters current knowledge.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…In line with this, several studies report that after control for abdominal AT and/or VAT, greater levels of LBSAT are associated with reduced risk of glucose intolerance, insulin resistance, dyslipidaemia and arterial stiffness [10][11][12][13][14][15][16]. However, extrapolation of this notion to suggest that, controlling for changes in abdominal adiposity, reductions in LBSAT during weight reduction may lead to deterioration in cardiometabolic profile, and thus increase the risk of type 2 diabetes and cardiovascular disease, counters current knowledge.…”
Section: Introductionmentioning
confidence: 64%
“…However, independent of changes in LBSAT, reductions in VAT and abdominal SAT were associated with improvements in cardiometabolic risk. A number of cross-sectional studies have previously shown that, after control for abdominal AT and/or VAT, greater levels of lower-body AT, specifically SAT, are associated with reduced risk of glucose intolerance, insulin resistance, dyslipidaemia and arterial stiffness [10][11][12][13][14][15][16]. While we could not corroborate this finding for glucose tolerance, the results of the current report demonstrate that, independent of VAT and abdominal SAT, greater lowerbody SAT is associated with lower triacylglycerol and higher HDL-cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have suggested that fat accumulated in peripheral depots, such as arms and legs, has less adverse effects on cardiovascular risk than other types of fat store. [15][16][17][18][19] Peripheral adipose tissue seems to have a high lipoprotein lipase activity and a low fatty acid turnover, 20 and to secrete higher quantities of adiponectin with antiatherogenic properties. 21 There is also evidence that adipocytes have distinct intrinsic characteristics (for example, fatty acid-binding proteins and enzymes of fat metabolism), which further contribute to the heterogeneity in free fatty acids handling by the different fat depots.…”
Section: Body Fat and Myocardial Infarctionmentioning
confidence: 99%
“…Only a few studies have addressed the cardiovascular role of peripheral fat mass, [15][16][17][18][19] which might be less atherogenic than abdominal fat, due to a low fatty acid turn-over, and a differential hormone production. 20,21 Moreover, because women and men have different patterns of fat distribution, 22 the association of peripheral fat with coronary outcomes might also vary with sex.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in postmenopausal women have revealed that trunk fat mass (TFM) measured using dual energy X-ray absorptiometry (DXA) is a strong independent predictor of insulin resistance and dyslipidemia [9][10][11][12] . Several studies have also suggested that in contrast with trunk fat, peripheral adiposity may attenuate both insulin resistance and dyslipidemia [10][11][12][13][14][15] or just lipid levels 16) in normal and overweight postmenopausal women. Although these differences may be due to differences in adipokine secretion from regional adipose tissue, a few studies have determined serum adipokine levels 17,18) .…”
mentioning
confidence: 99%